The COD Removal of Lime and Subsequent Acid Pretreated Partially Stabilised Leachate via Granular-Activated Carbon - Lennevey, Kinidi; Shanti Faridah, Salleh (Hindawi Publishing, 2020)
+is paper investigated the effectiveness of lime treatment and subsequent acid precipitation (using H2SO4) as a pretreatment of partially stabilised leachate. +is study obtained high removal efficiencies (>70%) from the lime and acid pretreated partially stabilised leachate. +e treatment of this wastewater with 10 g/L dosage of optimum lime (pH 12) at 25°C had led to the 41% COD elimination in the initial stages of pretreatment. Subsequent pH adjustment using 1 N sulfuric acid and granular-activated carbon adsorption in general revealed more than 92% removal of the 4 g/L of carbon dosage. +erefore, the results revealed that the adsorption of COD on the GAC stemmed from the kinetics rate of the pseudo-second-order.